The linguistic lesson in the interpretation of (Movable interpretations) For Yusuf Al-Asem Al-Kurdi (h 1002 h) - األظخاذ امىعاعس امسكخِر ودىس صاةص وصطف; األظخاذ امىعاعس امسكخِر ودىس شاكص ودىس صامح (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This research high lights on the life of commentator of the Noble Quran, named (Yousf Al-asamm Alkurdi). He is from Kurdistan of Iran and has a general knowledge, in a variety of sciences such as interpretation of the noble Quran, Arabic language, Islamic faith & Logic. In this paper, we have illustrated his method in his famous book (Manqul Al-tafaseer), particularly, the field of language investigations.